Telegram Application for Monitoring, Controlling and Protecting the Consumption of Household Electrical Appliances - Dicky Andrian Nugraha; Amirullah Amirullah (Faculty of Engineering, Universitas Tanjungpura, 2023)
Nominal electricity rates always increase, so it is necessary to take steps to save electricity consumption. One of the steps to save electricity consumption is taken by implementing a remote electrical equipment control system based on the Smart Home Internet of Things (IoT) system. Besides being able to save money, IoT systems are also able to help simplify work and human activities. This research aims to implement Internet of Things (IoT) equipment to monitor, control, protect, and On/Off timers for household electrical appliances monitored by the Telegram application and 16×2 LCD. Monitored system parameters i.e. voltage, current, frequency, power, energy, and electricity rates for each device. Device hardware i.e. Arduino Uno, 1 Channel Relay, PZEM-004t Voltage Sensor, NodeMCU ESP8266, and Current Sensor (Current Transformer). The equipment has been successfully tested on 10 different household appliances i.e. charged cellphones, fans, charged laptops, solder, iron, fluorescent lamp 36 W, television (TV), set-top box (STB)-TV, printer, and 5 W bulb lamp. The results showed that the prototype is capable of monitoring, controlling, protecting, and On/Off timer settings as well as being able to be monitored from home electric appliances both near and far using the 16×2 LCD and the Telegram application, respectively. The sensor tool using the Telegram application is able to measure/monitor the parameters of voltage, current and frequency at 10 loads with an average error value of 0.32%, 12.83% and 0.1% respectively compared to measurements using a Multimeter. The IoT prototype is also able to provide more complete, faster (4-5 sec) monitoring, control, protection, timer On/Off parameters and superior performance compared to devices designed by a number of previous researchers.